2020
DOI: 10.3389/fonc.2020.00394
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles Identified Novel Urine Biomarkers for Diagnosis and Prognosis of High-Grade Bladder Urothelial Carcinoma

Abstract: Bladder urothelial carcinoma (BC) has been identified as one of the most common malignant neoplasm worldwide. High-grade bladder urothelial carcinoma (HGBC) is aggressive with a high risk of recurrence, progression, metastasis, and poor prognosis. Therefore, HGBC clinical management is still a challenge. We performed the present study to seek new urine biomarkers for HGBC and investigate how they promote HGBC progression and thus affect the prognosis based on large-scale sequencing data. We identified the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…HGBC is more likely to have a high risk of recurrence, progression, and metastasis than LGBC. To our knowledge, both histological grade and tumor-node-metastasis (TNM) stage are closely related to prognosis [ 5 , 8 ]. However, there is no significant molecular marker able to predict prognosis or direct the treatment of UCB.…”
Section: Introductionmentioning
confidence: 99%
“…HGBC is more likely to have a high risk of recurrence, progression, and metastasis than LGBC. To our knowledge, both histological grade and tumor-node-metastasis (TNM) stage are closely related to prognosis [ 5 , 8 ]. However, there is no significant molecular marker able to predict prognosis or direct the treatment of UCB.…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing indicate that PAK1 knockdown leads to the reduction in GPx3 in the human SSC line. GPx3 has been reported as an important regulator for numerous cancers, e.g., lung cancer (An et al, 2018), esophageal carcinoma (Zhu et al, 2018, melanoma (Chen et al, 2016;Yi et al, 2019), prostate cancer (Chang et al, 2014;Chang et al, 2016;Chang et al, 2018), hepatocellular carcinoma (Qi et al, 2014), bladder cancer (Song et al, 2020), and ovarian cancer (Worley et al, 2019). For non-small-cell lung cancer, microRNA-196a manipulates the expression of GPx3 to inhibit the self-renewal ability of stem cells (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our finding is in line with several studies confirming a lower expression of GPX3 in the tumor tissue. Namely, analysis of data in TCGA and GTEx databases [ 44 , 45 ] revealed that GPX3 gene expression, associated with several tumor types, was higher in normal bladder tissue than in bladder carcinoma tissue [ 46 ]. Integrated pan-cancer analysis discussed that GPX3 was under expressed in 22 of 34 examined tumor tissue samples, including urothelial bladder carcinoma [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, latest research proposed GPX3 as a novel urine biomarker, based on relative expressions of GPX3 . Moreover, GPX3 level was significantly lower in urine of patients with bladder carcinoma than in controls [ 46 ]. Ultimately, GPX3 rs8177412 affects GPX3 gene expression and activity, in addition to altered levels of GSH due to the AA exposure.…”
Section: Discussionmentioning
confidence: 99%